IMPLEMENTASI KONSEP CSR DAN AKUNTANSI LINGKUNGAN DALAM REFLEKSI NILAI TOKOH PEWAYANGAN KRESNA - Ihsanul Windasari (POLITEKNIK LP3I JAKARTA, 2024)
This article explores the concepts of Corporate Social Responsibility (CSR) and environmental accounting with reference to traditional cultural values found in the story of the puppet character Kresna. This unique approach aims to see how Kresna's ethics and spirituality, such as justice, wisdom and responsibility, can be applied to contemporary business practices, particularly in terms of social and environmental responsibility. This research aims to reveal the relevance of the moral and ethical values taught by Kresna in the world of puppetry as a basis for more socially responsible and environmentally sustainable business practices. Using a literature study, this research examines literature on the story of Kresna and the concepts of CSR and environmental accounting, then relates them to form an ethical framework for the modern business world. The analysis shows that the values taught by Kresna can provide guidance in shaping a more ethical and environmentally sustainable business. For example, the values of justice and responsibility in Kresna's teachings encourage companies to be fair to various stakeholders and responsible for the social and environmental impacts of their business activities. In CSR, the application of this value is important amidst the pressures of globalization and increasing public awareness of environmental issues. By adopting local values as in the Kresna story, companies can create CSR programs that are not only profit-oriented or image-based, but also based on local wisdom. This study concludes that the values contained in the Kresna story can strengthen the ethical foundations of CSR and environmental accounting, providing a broader positive impact on society and the environment around the company. It also shows that the combination of traditional principles and modern business practices can generate greater benefits for all stakeholders and strengthen long-term goals in business sustainability.